2015
DOI: 10.1155/2015/276815
|View full text |Cite
|
Sign up to set email alerts
|

Serum Markers in Rheumatoid Arthritis: A Longitudinal Study of Patients Undergoing Infliximab Treatment

Abstract: Objective. The aim of this study was to investigate the clinical effect and serum markers in a cohort of rheumatoid arthritis patients with moderate to high disease activity, participating in an open clinical phase IV study conducted in Norway between 2001 and 2003 receiving infliximab treatment. Method. A total of 39 patients were studied, with a mean age of 54 years and 12-year disease duration. The analyses were performed using serum from patients at four assessment time points: baseline and 3, 6, and 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…VEGF is a serum marker for RA (Selaas et al, 2015). VEGF expression in atherosclerotic plaques is associated with plaque angiogenesis and progression (Phillips et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is a serum marker for RA (Selaas et al, 2015). VEGF expression in atherosclerotic plaques is associated with plaque angiogenesis and progression (Phillips et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] The magnitude in the elevation of proinflammatory cytokines in chronic HF is significantly less than what would be observed in cases of autoimmune diseases or acute infections, suggesting that low-grade chronic inflammation may be an important contributor to the maintenance or clinical deterioration of patients with established chronic HF. [9][10][11] Here, we will review what is known about the role of chronic inflammation in established HF. Importantly, we will highlight that although we have come to understand some of the intricate and contextdependent mechanisms in which inflammatory cells and pathways contribute to the development of HF in the acute setting, few of those insights have been extended to assessing the role of inflammation once chronic HF has been established.…”
mentioning
confidence: 99%
“…While in a different study before taking anti-rheumatic therapy, significant levels of IL-1β found in serum of 70 from 32 patients (> 10 pg/ml) while it was (0.35pg/ml) in serum of untreated RA patients . In the same study, a significant correlation was observed between the serum IL-1β levels at 6 months showing high levels of IL-1β before and even after 6 months of therapy [14].…”
Section: Levels Of Il-1β In Sera Samplesmentioning
confidence: 61%